Identification of the Political Role of Muhammad Husni Thamrin in 1919-1941 as the Development of Indonesian Historical Material in the Middle School Class - Octria Dwi Hastuti; Djono Djono; Isawati Isawati (PAEDAGOGIA, 2020)
: The purposes of this research are to describe: the background of Muhammad Husni Thamrin's life, political conditions in the Dutch East Indies from 1919-1941, the political roles period 1919-1941, period  1919-1941 as the development of Indonesian history materials for XI grade of high school. This research uses the historical method.  The research procedure was carried out through 4 stages of activities namely: heuristics, criticism, interpretation, and historiography. Based on the results of the study it can be concluded: Muhammad Husni is work experience before becoming a member of the board included an internship at the Kepatihan office and the Batavia's Karesidenan office, The Political Situation of the Dutch East Indies in 1919-1941 based on Colonial Political policy, divided into 2 periods namely reactionary politics (1918-1930) the last decade of the Dutch East Indies (1930-1942) where national movements were centered on the People's Council and the cooperative party, Political role in 1919-1941 within. the Dutch East Indies government was a member of the City Council of Batavia and People's Council. Muhammad Husni Thamrin was also active in parties and other organizations or associations, such as PPPKI, Parindra, and GAPI, Political Role of Muhammad Husni Thamrin as the development of Indonesian History materials for XI Grade of High School could be used as a source of material development by an Indonesian history teacher in XI grade of KD 3.4 "respecting the values of youth oaths and their meaning for national life in Indonesia today" with the subject matter of the Education and Indonesian National Movement.